Enhanced low-temperature ionic conductivity via different Li+ solvated clusters in organic solvent/ionic liquid mixed electrolytes. Issue 36 (1st September 2016) - Aguilera, Luis; Scheers, Johan; Matic, Aleksandar
Abstract : We investigate Li + coordination in mixed electrolytes based on ionic liquids (ILs) and organic solvents and its relation with the macroscopic properties such as phase behaviour and ionic conductivity. Abstract : We investigate Li + coordination in mixed electrolytes based on ionic liquids (ILs) and organic solvents and its relation with the macroscopic properties such as phase behaviour and ionic conductivity. Using Raman spectroscopy we determine the solvation shell around Li + in mixtures formed by the IL N -butyl- N -methylpyrrolidinium bis(trifluoromethanesulfonyl)imide, the organic solvents ethylene carbonate and dimethyl carbonate (EC : DMC 1 : 1), and the salt LiTFSI. We find that the organic solvent molecules preferentially solvate Li + as long as there are enough of them. Our results are consistent with a model where Li(EC)3 (DMC)1 and Li(EC)2 (DMC)2 are the main complexes formed by the organic solvent molecules and where TFSI − mainly participates in Li(TFSI)2 − clusters. As the amount of organic solvent is increased, the number of TFSI − around Li + rapidly decreases showing a higher affinity of the organic solvents to solvate Li + . The changes in the local configurations are also reflected in the ionic conductivity and the phase behaviour. The formation of larger clusters leads to a decrease in the conductivity, whereas the presence of several different clusters at intermediate compositions effectively hinders crystallization at low temperatures. The result is an enhanced low-temperature ionic conductivity in comparison with the pure IL or organic solvent electrolytes.